2022
DOI: 10.3390/ijms23179572
|View full text |Cite
|
Sign up to set email alerts
|

Mitochonic Acid 5 Improves Duchenne Muscular Dystrophy and Parkinson’s Disease Model of Caenorhabditis elegans

Abstract: Mitochonic Acid 5 (MA-5) enhances mitochondrial ATP production, restores fibroblasts from mitochondrial disease patients and extends the lifespan of the disease model “Mitomouse”. Additionally, MA-5 interacts with mitofilin and modulates the mitochondrial inner membrane organizing system (MINOS) in mammalian cultured cells. Here, we used the nematode Caenorhabditis elegans to investigate whether MA-5 improves the Duchenne muscular dystrophy (DMD) model. Firstly, we confirmed the efficient penetration of MA-5 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…Therefore, we monitored mitochondrial Ca 2+ changes in CEPs in young gravid adults only after treatment with low dose of rotenone (mitochondrial complex I inhibitor). Previous observations revealed that 2 mM-rotenone treatment for 24 h similarly increased CEPs' puncta despite young gravid adults, and MA-5 administration suppress the increase in puncta 9 . We therefore used the same treatment conditions to study whether low-dose rotenone increases mitochondrial calcium levels in CEPs and, if so, whether MA-5 can suppress it.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Therefore, we monitored mitochondrial Ca 2+ changes in CEPs in young gravid adults only after treatment with low dose of rotenone (mitochondrial complex I inhibitor). Previous observations revealed that 2 mM-rotenone treatment for 24 h similarly increased CEPs' puncta despite young gravid adults, and MA-5 administration suppress the increase in puncta 9 . We therefore used the same treatment conditions to study whether low-dose rotenone increases mitochondrial calcium levels in CEPs and, if so, whether MA-5 can suppress it.…”
Section: Introductionmentioning
confidence: 84%
“…On the other hand, MA-5 administration reduced mitochondrial Ca 2+ overload induced by aging and rotenone treatment (Fig. 1,2), as well as dys-1 (eg33) mutation 9 , while maintaining MCU activity. These results clearly demonstrate that MA-5 contributes to the maintenance of mitochondrial homeostasis by inhibiting excessive Ca 2+ accumulation, rather than inhibiting normal Ca 2+ uptake into mitochondria.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Nematodes treated with rotenone displayed loss of dopaminergic neurons, growth and motility defects as well as mitochondrial deficits [ 83 , 84 ]. However, a novel synthesized compound, mitochonic acid 5 (MA-5) derived from plant hormone Indole-3-Acetic Acid (IAA), has been shown to significantly reduce mitochondrial ROS elevation and degeneration of dopaminergic neurons, probably through its interaction with mitofilin as previously shown in mammalian cells [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Symptoms of PD include motor and non-motor symptoms, such as rest tremor, bradykinesia, rigidity, loss of postural reflexes and depression, and can be mostly traced to the loss of dopaminergic neurons in the substantia nigra, which leads to a reduction in dopamine release [ 79 , 80 ].…”
Section: Parkinson’s Diseasementioning
confidence: 99%